Comparison of Ground Motion Prediction Equation (GMPE) Analysis of the Bandung Earthquake 22 January 2022 - Takhul Bakhtiar (MO.RI Publishing, 2022)
The value of ground acceleration in an area due to an earthquake that occurs can have different values. One of the factors that influence this is the geological conditions in the area. The purpose of this study was to compare the Peak Ground Acceleration (PGA) values in the area using several Empirical Ground Motion Equation Prediction (GMPE) formulas such as Inan et al. (1996), Katayama (1974) and Peng et al. (1985) with results that are read on the accelerograph. This study uses earthquake data from the and several station networks Meteorology, Climatology and Geophysics Agency (BMKG) in the West Java region. The results of the analysis show that the empirical formula that is close to the readable value on the accelerograph record is the empirical formula of Inan et al. (1996). Thus the empirical formula is suitable for calculating PGA values in the region.